Screening del rischio da movimentazione manuale pazienti con metodo MAPO / Screening of patient manual handling risk using the MAPO method - Battevi, N.; Menoni, O.; Alvarez-Casado, E. (La Medicina del Lavoro, 2012)
Summary«Screening of patient manual handling risk using the MAPO method». Background: International standards draw attention to the steps that risk assessment should follow to first identify hazards, then proceed to risk evaluation and lastly, if necessary, risk assessment. The same logic also applies to risk assessment of manual patient handling. Objectives: To check appropriateness of approach to “risk evaluation” of manual patient handling using MAPO, a cross sectional study was carried out aimed at checking the relationship between this new risk assessment model (MAPO screening) and occurrence of acute low back pain. Methods: After proper training the MAPO screening method was used to assess risk of manual handling of patients in 31 wards, covering 411 exposed subjects employed in geriatric hospitals belonging to the UNEBA (National Union Institutions and Social Welfare Initiatives) of the Veneto Region. At the same time health data were collected on the occurrence of low back pain episodes during the last year both in the group of exposed subjects and in an external reference group (237 subjects). Risk and clinical assessment data were verified and checked by the EPM research unit. Logistic analysis was used as a method to evaluate the relationship between MAPO screening risk index and acute low back pain. Results: Investigating the relationship between acute low back pain episodes and levels of MAPO screening index, carried out only on exposed subjects who reported working for at least 30 hours per week (N=178), showed definitely positive trends: for MAPO screening index of exposure levels between 1.51 and 5, OR were double (OR=2.22; IC 95% 0.88-5.63) whereas for index levels exceeding 5, OR were about 4 (OR=3.77; IC 95% 1.33-10.74). These results did not show significant differences when correcting the analysis for confounding factors such as gender and age classes. Conclusions: The results of the study indicate that the proposed method, "MAPO screening”, can be a useful tool to estimate risk due to manual handling of patients and can also be used to test the efficacy of preventive measures.RiassuntoLa normative internazionali pongono l’accento alle fasi che debbono caratterizzare la valutazione del rischio che in sequenza dovrebbero prevedere prima l’identificazione dei pericoli poi la stima del rischio ed infine, se necessario la valutazione del rischio. A questa logica soggiace anche la valutazione del rischio da movimentazione manuale dei pazienti. Per verificare l’adeguatezza di un approccio alla “stima del rischio”, da movimentazione manuale pazienti, con il metodo MAPO, è stato condotto uno studio trasversale volto a verificare la relazione fra questo nuovo modello di valutazione del rischio (MAPO Screening) e l’occorrenza di episodi di lombalgia acuta. Dopo adeguato training è stato valutato il rischio da movimentazione manuale di pazienti con il metodo di Screening MAPO in 31 reparti, con 411 esposti, di Residenze Sanitarie per Anziani appartenenti al circuito UNEBA della Regione Veneto. Contestualmente sono stati raccolti dati sanitari circa l’occorrenza di episodi di lombalgia acuta occorsi nell’ultimo anno sia nel gruppo degli esposti che in un gruppo di riferimento esterno (n=237), spazio e tempo specifico. Sia i dati relativi al rischio che quelli riferiti all’accertamento clinico  sono stati oggetto di tutoraggio e verifica da parte dell’Unità di Ricerca EPM. L’analisi della relazione fra episodi di lombalgia acuta e livelli dell’indice “MAPO screening”, effettuata con analisi di tipo logistico e per i soggetti esposti che hanno dichiarato di lavorare per almeno 30 ore settimanali (n°=178), ha mostrato trend francamente positivi: per livelli di esposizione dell’indice “MAPO screening” compresi fra 1,51 e 5 l’OR corretto è risultato doppio (OR=2,22; IC 95% 0,88-5,63) mentre per livelli di indice superiore a 5 gli OR sono risultati pari a circa 4 (OR=3,77; IC 95% 1,33-10,74). Tali risultati non hanno mostrato differenze significative correggendo l’analisi per fattori di confondimento quali il sesso e le classi d’età. I risultati dello studio indicano che il metodo proposto, “MAPO screening”, può costituire uno strumento utile nella stima del rischio da movimentazione manuale pazienti e si presta anche ad un utilizzo nell’ambito delle verifiche di efficacia degli interventi di prevenzione adottati.